IJCM_409A: Prevalence And Pattern of Self-Medication With Antibiotics: A Community- Based Cross-Sectional Study From South-East Delhi - Jabeen Roshan; Shaikh Aqsa; Gautam Richa; Nabi Nusrat (Wolters Kluwer Medknow Publications, 2024)
Background: Antibiotics are commonly self-medicated drugs worldwide, with over 50% purchased and used without a prescription. Antibiotic resistance has emerged as a global public health concern. Although many studies have been conducted worldwide to study the prevalence and pattern of self-medication with antibiotics and associated socio-demographic factors (SMA), very few have been conducted in India, and no such studies have been conducted in Delhi in community setup, especially in post-pandemic setup. Objective: 1. To estimate the prevalence and pattern of self-medication with antibiotics among the adults residing in the field practice areas of a medical college in South-East Delhi. 2. To determine the socio-demographic factors and their association with self-medication with antibiotics among the study subjects. Methodology: A cross-sectional analytical study was conducted in South-East Delhi. The sample size was calculated as 200 considering an absolute error of 5% at a 95% level of significance. Simple random sampling was done to select households by using a Random number generator. The total sample size of 200 was distributed proportionately between the UHTC and RHTC, according to Probability Proportional to Size (PPS). One individual from each selected household of age = 18 years who has used antibiotics in the past 3 months and met the eligibility criteria was included in the study. A self-designed, pre-tested, validated, structured questionnaire was used to collect the data. Results: 71(35%) out of 200 of the participants practiced SMA. Nearly 42% of them lived in urban areas. 30% had an education level of high school and above. The Chi-square test revealed that the participant's level of education was significantly associated with SMA. The frequency of SMA ranges from one to a maximum of five times in the past 3 months. 69% of the respondents administered antibiotics twice in the past 3 months. The indications for SMA were fever (34%), followed by cold and flu (23%) and UTI (14%). Most of the participants who practiced SMA obtained antibiotics from the pharmacy (75%) followed by leftovers from previous treatment (17%). Conclusion: The study revealed that more than one-third of the respondents practiced SMA. The findings from the present study indicate the necessity of activating antimicrobial stewardship programs throughout the country, as well as implementing effective legislation to prohibit dispensing antibiotics without prescription.